Hypoglycemic effect of camel milk powder in type 2 diabetic patients: A randomized, double‐blind, placebo‐controlled trial. Issue 8 (29th June 2021) - Zheng, Yajie; Wu, Fang; Zhang, Ming; Fang, Bing; Zhao, Liang; Dong, Lijie; Zhou, Xiaojuan; Ge, Shaoyang
Abstract: Fresh camel milk was widely accepted to help to prevent and control of diabetes, especially in Africa, Middle East, and cooler dry areas of Asia. In this study, type 2 diabetic patients were enrolled to supplement with 10 g of camel milk powder twice a day for 4 weeks ( n = 14), cow milk powder served as the placebo ( n = 13). It was found that camel milk supplement decreased fasting blood glucose, 2‐hr postprandial blood glucose, serum content of total cholesterol, resistin, and lipocalin‐2. There was also a significant increase in serum content of osteocrin, amylin, and GLP‐1in camel milk group, indicating an improvement on adipose tissue and skeletal muscle. Camel milk powder supplement significantly enriched the relative abundance of Clostridium_sensu_stricto_1 and [Eubacterium]_eligens_group compared with cow milk after the 4‐week intervention. This study suggested that camel milk powder can be used as a functional food help to treat type 2 diabetes. Abstract : It was found that camel milk supplement decreased fasting blood glucose, 2‐hr postprandial blood glucose, serum content of total cholesterol, resistin, and lipocalin‐2. There was also a significant increase in serum content of osteocrin, amylin, and GLP‐1in camel milk group, indicating an improvement on adipose tissue and skeletal muscle. Camel milk powder supplement significantly enriched the relative abundance of Clostridium_sensu_stricto_1 and [Eubacterium]_eligens_group compared with cow milk after the 4‐week intervention.